Implications of the small number of distinct ligand binding pockets in proteins for drug discovery, evolution and biochemical function. Issue 6 (15th March 2015) - Skolnick, Jeffrey; Gao, Mu; Roy, Ambrish; Srinivasan, Bharath; Zhou, Hongyi
Graphical abstract: Abstract: Coincidence of the properties of ligand binding pockets in native proteins with those in proteins generated by computer simulations without selection for function shows that pockets are a generic protein feature and the number of distinct pockets is small. Similar pockets occur in unrelated protein structures, an observation successfully employed in pocket-based virtual ligand screening. The small number of pockets suggests that off-target interactions among diverse proteins are inherent; kinases, proteases and phosphatases show this prototypical behavior. The ability to repurpose FDA approved drugs is general, and minor side effects cannot be avoided. Finally, the implications to drug discovery are explored.